REFLEKSIVITAS DAN KEINTIMAN PADA FLIGHT ATTENDANT YANG MENJALANI LONG-DISTANCE ROMANTIC RELATIONSHIP - Monica, Arvela Cahya; Ranteallo, Ikma Citra; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
The present research focuses on the singular experiences of flight attendants in long-distance relationships and the various strategies they employ to overcome the obstacles that arise due to this arrangement. The study has revealed that these individuals rely on several techniques, including self-reflection and self-soothing, to manage the stress and ambiguity that accompany being apart from their significant others for extended periods. Additionally, they use multiple communication platforms, such as chat, phone, and video calls, to stay connected with their partners, provide reassurance, and remain adaptable in their relationships. To foster intimacy in their relationships, flight attendants place considerable emphasis on principles such as equality, honesty, freedom, and open communication. They are attentive to their partners' needs and preferences and willing to make sacrifices to ensure both parties feel heard and valued. By prioritizing these principles and practices, flight attendants can successfully navigate the challenges of long-distance relationships and maintain strong, healthy connections with their partners.